Jus Gentium and the Primary Principles of International Law - Задорожна, Світлана (European Journal of Law and Public Administration., 2019)
Jus gentium is a system of rules of law that takes its origins even from the inter-ethnic Roman law, that contains the basic principles of regulation of both internal and international law. Thanks to the jus gentium the customary general principles of law and the general principles of international law have been transferred from the ancient law to the middle ages when they were established as well as. Most of the general principles of law of peoples have become today the imperative principles of international law, and the general principles, that were developed by the Roman jurists, foremost, it is the principles of equality, justice, and humanism, that were reciprocated by the law of European states, eventually transformed into the general principles of national law, and through them - the basic principles of international law. Jus gentium made a significant impact on the formation of the basic principles of international law on the European continent, and later on - universal international law. In the structure of Roman law, three main elements were distinguished: jus civile, jus naturale, jus gentium. The main source of international law is usually jus gentium, but today international law also accumulates the general principles of law (jus naturale) and universally recognized principles of domestic law (jus civile), which is confirmed by the norm of art. 38 of the Charter of the United Nations. In jus gentium, we find the origins of the principle of sovereignty, establishes the principle of bona fide compliance, the principle of mutual courtesy (comitas gentium), develops the principle of succession, there are first principles of territorial space, the principle of res judicata - the principle of binding for the parties to the court decision. Most procedural and technical principles have their source jus gentium.
Keywords: jus gentium, principles of international law, general international law, history of international law.